Plastic analysis of a laterally loaded vertical pile shaft embedded in cohesive soil - Ghosh C. (My University, 2025)
The lateral load capacity of a vertical pile depends essentially on the relative stiffness of the pile and of the surrounding soil. This is important for cases, where large horizontal loads must be resisted or where the surrounding soil is very soft, causing large lateral displacements of the pile-soil system. This paper presents lower bound analysis of a laterally loaded vertical pile (with both ends free) shaft embedded in cohesive soil. Three different cases corresponding to feasible horizontal soil pressure distributions against the pile shaft have been considered. Based on force and moment equilibrium conditions of the pile-soil system, results are presented in parametric form.